Benefits of Increased Railway Safety and Reliability and their Evaluation - Hromádka, Vít; Korytárová, Jana; Vítková, Eva; Seelmann, Herbert; Funk, Tomáš (University North, 2023)
The paper focuses on the presentation of key results of the project of applied research oriented on evaluation of the increased safety and reliability of the railway network due to the implementation of relevant railway network projects and their projection into the investment project socio-economic evaluation using Cost-Benefit Analysis. The subject research described in the article is the design and verification of the functionality of the methodological procedure for the evaluation of these benefits for their further use in the assessment of public projects on railways. The methodological part summarizes the basic outputs of the previous research. These outputs were subsequently applied at the formulation of basic rules for the assessment of benefits connected with increased railway reliability and safety, which were later processed into the form of simplified methodological procedure. The simplified approach uses average data on the occurrence impact for the entire railway network, broken down into line and station sections. The functionality of individual approaches was checked on case studies of actually implemented projects.

The paper focuses on the presentation of key results of the project of applied research oriented on evaluation of the increased safety and reliability of the railway network due to the implementation of relevant railway network projects and their projection into the investment project socio-economic evaluation using Cost-Benefit Analysis. The subject research described in the article is the design and verification of the functionality of the methodological procedure for the evaluation of these benefits for their further use in the assessment of public projects on railways. The methodological part summarizes the basic outputs of the previous research. These outputs were subsequently applied at the formulation of basic rules for the assessment of benefits connected with increased railway reliability and safety, which were later processed into the form of simplified methodological procedure. The simplified approach uses average data on the occurrence impact for the entire railway network, broken down into line and station sections. The functionality of individual approaches was checked on case studies of actually implemented projects.
Benefits of Increased Railway Safety and Reliability and their Evaluation
Keywords: benefits; economic efficiency; occurrences; railways; safety and reliability; social impacts; benefits; economic efficiency; occurrences; railways; safety and reliability; social impacts